Flipping the Classroom for higher Education Learners to Improve Productive and Receptive Skills - Cristina (Tejuelo: Didáctica de la Lengua y la Literatura)
This study examines the ability of Tourism students to deal with customer complaints by using the flipped classroom approach combined with the implementation of the online VoiceThread programme. The study was carried out with a group of 49 EFL students in the Degree of Tourism at the University Complutense of Madrid. The study was carried out in 3 phases: (1) students were provided with audio material containing some useful expressions related to customers’ complaints. This material was made available on the Virtual Platform (Campus Virtual) so students could consult it as they needed before the following class. (2) In the computing room, students were asked to listen to a customer complaint and to give a solution by recording their own voices. (3) In order to gather students’ opinions about this experimental activity, students were asked to fill in a Google form questionnaire. Overall, the results of the study have shown the positive impact of this method on the teaching/learning process in the EFL classes for Tourism students, contributing to their motivation and development of their professional skills.